Early-life exposure to phthalates and nanoplastics alters gut microbiota and intestinal morphophysiology in rat dams and male offspring - Natália Magosso; Matheus Naia Fioretto; Isabella Fávaro; Patrick Vieira de Souza; Mirella Franco Moreira; Vanessa Aguiar Rocha; Felipe Cristiano Barbosa; Josias Rodrigues; Wellerson Rodrigo Scarano (Toxicology, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Changes in serum lactate and creatine kinase levels in free-living Geoffroy’s (Phrynops geoffroanus) side-necked turtle captured using funnel traps - Nicole Wirschke de Azevedo; Rafael Martins Valadão; Ana Paula Gomes Lustosa; Patrick Luiz Bola Gonsales; Ana Letícia Rodrigues Marques; Marina Marangoni; Ademar Francisco Fagundes Meznerovvicz; Andriel Gustavo Felichak; Paulo Henrique Braz (Environmental Monitoring and Assessment, 2026)
Capture techniques are widely employed in wildlife monitoring programs, yet confinement and handling may induce transient physiological alterations that complicate interpretation of biochemical parameters. This study evaluated temporal changes in serum lactate and creatine kinase (CK) concentrations in free-living Phrynops geoffroanus captured using funnel traps in southern Brazil. Ten adult turtles (5 males, 5 females) were sampled at two time points: immediately after transport from capture sites (T0) and 24 h later (T24). Paired analyses indicated a significant decrease in lactate concentrations from T0 (90.6 ± 44.0 mg/dL) to T24 (38.2 ± 20.8 mg/dL; p = 0.0044), consistent with recovery from acute anaerobic activation. In contrast, CK activity increased significantly from T0 (2,227.8 ± 2,776.9 U/L) to T24 (8,131.0 ± 5,306.7 U/L; p = 0.0012), suggesting delayed enzymatic release associated with muscular strain. These divergent temporal patterns reflect distinct physiological mechanisms and biomarker kinetics following capture. The results highlight the importance of considering sampling latency when interpreting post-capture biochemical values in ecological studies. Funnel traps proved operationally effective, but confinement duration should be carefully managed to minimize physiological stress. Incorporating temporal context into capture protocols can improve the accuracy of physiological assessments in environmental monitoring programs.

Stratigraphic and paleoenvironmental significance of palustrine deposits in bioclastic successions: Morro do Chaves formation, Northeast Brazil - Marila Andrade; Patrick Führ Dal’ Bó; Amanda Rodrigues; Julia Favoreto; Leonardo Borghi; Maurícius Nascimento Menezes (Journal of South American Earth Sciences, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Natural pigments as eco-friendly staining agents: evaluation of β-carotene-rich carrot and betanin-rich beetroot extracts for bacterial biofilm visualisation - Eliana Câmpelo Lago; Andreanne Gomes Vasconcelos; Alyne Rodrigues de Araújo-Nobre; Laila Salmen Espindola; Patrick Veras Quelemes; Daniel Dias Rufino Arcanjo; Massimo Lucarini; Alessandra Durazzo; José Roberto de Souza de Almeida Leite (Natural Product Research, 2025)

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Turning up the heat on skeletal muscle adaptations and neuromuscular function: key considerations for passive heating prescription and best practices - Patrick Rodrigues; Geoffrey M. Minett; Lucas B. R. Orssatto (European Journal of Applied Physiology, 2025)
Despite compelling evidence supporting the benefits of passive heat therapy in promoting skeletal muscle adaptation and enhancing neuromuscular function, the topic remains debated. Some recent studies report no significant effects on muscle protein synthesis, muscle mass, recovery, strength, or power. This raises critical questions: is passive heat therapy not actually effective? Or do these discrepancies reflect inconsistencies in study protocols and an overgeneralisation of the term passive heating ? Despite its growing recognition as a health treatment, exercise mimetic, and tool for sport performance and recovery, the interpretation of outcomes is often simplistic or misinformed. In this opinion article, we discuss the disparities in the literature and highlight the risks of oversimplification, such as the binary view that passive heat therapy either “works” or “does not work.” We also propose incorporating the FITT (Frequency, Intensity, Time, and Type) principles from exercise science into thermal therapy research to enhance methodological consistency and clarity. By adopting a more structured and rigorous approach, the field can better realise the potential of passive heat therapy as a scientifically grounded intervention for both health and sport performance applications.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Effect of torrefaction severity on the energy recovery from amazonian wood residues for decentralized energy conversion systems - Edgar A. Silveira; Giulia Cruz Lamas; Pedro Paulo de O. Rodrigues; Normando P.B. Souto; Bruno Sant’Anna Chaves; Luiz Gustavo Oliveira Galvão; Lucélia A. Macedo; Juliana Sabino Rodrigues; Sandra M. Luz; Patrick Rousset; Thiago de Paula Protásio (Biomass and Bioenergy, 2025)

Mercury in river samples with artisanal and small-scale gold mining influence: The case of the upper Madeira River Basin (Brazil/Bolivia) - Julia Mançano Quintarelli; Jérémie Garnier; João Pedro Rudrigues de Souza; Myller de Sousa Tonhá; Uidemar Morais Barral; Henrique Llacer Roig; Jean-Michel Martinez; William Santini; Oscar Puita; Patrick Seyler; Vinicius Kutter; Jurandir Rodrigues Souza (Journal of South American Earth Sciences, 2024)

One size does not fit all: Methodological considerations and recommended solutions for intramuscular temperature assessment - Patrick Rodrigues; Lucas B.R. Orssatto; Anne Hecksteden; Gabriel S. Trajano; Geoffrey M. Minett (Journal of Thermal Biology, 2024)

Variability of the equatorial ionization anomaly over the South American sector: Effects of electric field and effective meridional wind - Solomon Otoo Lomotey; Jonas Rodrigues de Souza; Cristiano Max Wrasse; Hisao Takahashi; Diego Barros; Cosme Alexandre Oliveira Barros Figueiredo; José Humberto Andrade Sobral; Fábio Egito; Patrick Essien; Toyese Tunde Ayorinde; Anderson Vestena Bilibio; Nana Ama Browne Klutse (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Potential of different strategies to increase intramuscular fat deposition in sheep: A meta-analysis study - Rodrigo de Nazaré Santos Torres; Caren Paludo Ghedini; Luis Artur Loyola Chardulo; Welder Angelo Baldassini; Rogério Abdallah Curi; Guilherme Luis Pereira; Jon Patrick Schoonmaker; Marco Tulio Costa Almeida; Ciniro Costa; Otavio Rodrigues Machado Neto (Small Ruminant Research, 2024)

Transpiration from crystalline unconfined aquifers as the cause of groundwater salinization in a semiarid area of Brazil - Marjorie Beate Kreis; Jean-Denis Taupin; Patrick Lachassagne; Nicolas Patris; Eduardo Sávio Passos Rodrigues Martins (Hydrogeology Journal, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Diversity of fungal microbiome obtained from plant rhizoplanes - Simone Lupini; Hang N. Nguyen; Demosthenes Morales; Geoffrey L. House; Sachin Paudel; Patrick S.G. Chain; Debora F. Rodrigues (Science of The Total Environment, 2023)

Midterm change in rainfall distribution in north and central Benin: implications for agricultural decision making - Moudjahid Akorédé Wabi; Wouter Vanhove; Rodrigue Idohou; Achille Hounkpèvi; Romain Lucas Glèlè Kakaï; Patrick Van Damme (Environment, Development and Sustainability, 2023)

Selective tumor cell growth inhibition by lignans and a seco -triterpenoid from Combretum mellifluum - Patrick da Silva Mirowski; Mariáh Ojeda; Luiz Gustavo Kollet; Talita Vilalva Freire; Arnildo Pott; Walmir Silva Garcez; Renata Trentin Perdomo; Fernanda Rodrigues Garcez (Natural Product Research, 2022)

Potential role of passively increased muscle temperature on contractile function - Patrick Rodrigues; Gabriel S. Trajano; Ian B. Stewart; Geoffrey M. Minett (European Journal of Applied Physiology, 2022)
Declines in muscle force, power, and contractile function can be observed in older adults, clinical populations, inactive individuals, and injured athletes. Passive heating exposure (e.g., hot baths, sauna, or heated garments) has been used for health purposes, including skeletal muscle treatment. An acute increase in muscle temperature by passive heating can increase the voluntary rate of force development and electrically evoked contraction properties (i.e., time to peak twitch torque, half-relation time, and electromechanical delay). The improvements in the rate of force development and evoked contraction assessments with increased muscle temperature after passive heating reveal peripheral mechanisms’ potential role in enhancing muscle contraction. This review aimed to summarise, discuss, and highlight the potential role of an acute passive heating stimulus on skeletal muscle cells to improve contractile function. These mechanisms include increased calcium kinetics (release/reuptake), calcium sensitivity, and increased intramuscular fluid.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Removal of Methyl Violet Dye by Adsorption Process on Hydrogen Titanate Nanotubes: Experimental-Theoretical Study - Daniela Kelly dos Santos; Renata Treméa; Eudes Lorençon; Patrick Rodrigues Batista; Lucila Adriani de Almeida Coral; Fatima de Jesus Bassetti (Water, Air, & Soil Pollution, 2022)

Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Jan H. Landsberg; Maki Tabuchi; David S. Rotstein; Kuttichantran Subramaniam; Thais C. S. Rodrigues; Thomas B. Waltzek; Nicole I. Stacy; Patrick W. Wilson; Yasunari Kiryu; Francisco A. Uzal; Martine de Wit (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee ( Trichechus manatus latirostris ). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.

Muscle temperature kinetics and thermoregulatory responses to 42 °C hot-water immersion in healthy males and females - Patrick Rodrigues; Gabriel S. Trajano; Lee Wharton; Geoffrey M. Minett (European Journal of Applied Physiology, 2020)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Nanoemulsions with oleoresin of Copaifera reticulata (Leguminosae) improve anthelmintic efficacy in the control of monogenean parasites when compared to oleoresin without nanoformulation - Dayna Filocreão Malheiros; Icaro Rodrigues Sarquis; Irlon Maciel Ferreira; Patrick Delgado Mathews; Omar Mertins; Marcos Tavares‐Dias (Journal of Fish Diseases, 2020)
This study compared the in vitr o anthelmintic activity of Copaifera reticulata oleoresin (200, 400, 600, 800 and 1,000 mg/L) and of nanoemulsions prepared with this oleoresin (50, 100, 150, 200 and 250 mg/L) against monogeneans on the gills of Colossoma macropomum . The major compounds present in the oleoresin of C. reticulata were γ‐macrocarpene (14.2%), α‐bergamotene (13.6%), β‐selinene (13.4%) and β‐caryophyllene (11.7%). All concentrations of the nanoemulsion and the oleoresin without nanoformulation showed anthelmintic efficacy against monogeneans, and higher concentrations led to more rapid parasite mortality. Structural damages to the tegument of the parasites exposed to C. reticulata oleoresin were observed with scanning electron microscopy. At two hours of exposure, fish showed 100% tolerance to all nanoemulsion concentrations used in the in vitro assays, whereas 100% mortality was shown in the fish exposed to the oleoresin without nanoformulation after one hour. The results of this study suggest that nanoemulsions with oleoresin of C. reticulata have advantages in the control and treatment of monogenean infections in C. macropomum when compared to the oleoresin without nanoformulation. In addition, since nanoemulsions with the C. reticulata oleoresin are safe to control monogeneans, the efficacy of these nanoformulations may be assayed in therapeutic baths to treat C. macropomum infected by monogeneans.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Erratum to: Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Origin and introduction history of the least weasel (Mustela nivalis) on Mediterranean and Atlantic islands inferred from genetic data - Mónica Rodrigues; Arthur R. Bos; Patrick J. Schembri; Ricardo F. de Lima; Petros Lymberakis; Lluís Parpal; Michele Cento; Sandrine Ruette; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Biological Invasions, 2017)

Diet‐related gut bacterial dysbiosis correlates with impaired development, increased mortality and Nosema disease in the honeybee ( Apis mellifera ) - Patrick W. Maes; Pedro A. P. Rodrigues; Randy Oliver; Brendon M. Mott; Kirk E. Anderson (Molecular Ecology, 2016)
Dysbiosis, defined as unhealthy shifts in bacterial community composition, can lower the colonization resistance of the gut to intrinsic pathogens. Here, we determined the effect of diet age and type on the health and bacterial community composition of the honeybee ( Apis mellifera ). We fed newly emerged bees fresh or aged diets, and then recorded host development and bacterial community composition from four distinct regions of the hosts’ digestive tract. Feeding fresh pollen or fresh substitute, we found no difference in host mortality, diet consumption, development or microbial community composition. In contrast, bees fed aged diets suffered impaired development, increased mortality and developed a significantly dysbiotic microbiome. The consumption of aged diets resulted in a significant reduction in the core ileum bacterium Snodgrassella alvi and a corresponding increase in intrinsic pathogen Frischella perrara . Moreover, the relative abundance of S. alvi in the ileum was positively correlated with host survival and development. The inverse was true for both F. perrara and Parasacharibacter apium . Collectively, our findings suggest that the early establishment of S. alvi is associated with healthy nurse development and potentially excludes F. perrara and P. apium from the ileum. Although at low abundance, establishment of the common midgut pathogen Nosema spp. was significantly associated with ileum dysbiosis and associated host deficiencies. Moreover, dysbiosis in the ileum was reflected in the rectum, mouthparts and hypopharyngeal glands, suggesting a systemic host effect. Our findings demonstrate that typically occurring alterations in diet quality play a significant role in colony health and the establishment of a dysbiotic gut microbiome.

Taxonomic status and origin of the Egyptian weasel (Mustela subpalmata) inferred from mitochondrial DNA - Mónica Rodrigues; Arthur R. Bos; Richard Hoath; Patrick J. Schembri; Petros Lymberakis; Michele Cento; Wissem Ghawar; Sakir O. Ozkurt; Margarida Santos-Reis; Juha Merilä; Carlos Fernandes (Genetica, 2016)

Toxic effects of the ingestion of water-soluble elements found in soil under the atmospheric influence of an industrial complex - Flavio Manoel Rodrigues da Silva Júnior; Patrick Ferreira Silva; Edariane Menestrino Garcia; Roberta Daniele Klein; Gianni Peraza-Cardoso; Paulo Roberto Baisch; Vera Maria Ferrão Vargas; Ana Luíza Muccillo-Baisch (Environmental Geochemistry and Health, 2013)

Integrated indicators for performance assessment of traditional agroforestry systems in South West Cameroon - Geraldo Stachetti Rodrigues; Inacio de Barros; Eugène Ejolle Ehabe; Patrick Sama Lang; Frank Enjalric (Agroforestry Systems, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)